Use of myoelectric signals to command mobile entertainment robot by disabled children: Design and control architecture - Ferasoli-Filho, Humberto [UNESP]; Caldeira, Marco Antonio Corbucci [UNESP]; Pegoraro, Renê [UNESP]; Dos Reis Alves, Silas Franco; Valadão, Carlos; Bastos-Filho, Teodiano Freire (Institute of Electrical and Electronics Engineers (IEEE), 2012)
Severely disabled children have little chance of environmental and social exploration and discovery. This lack of interaction and independency may lead to an idea that they are unable to do anything by themselves. In an attempt to help children in this situation, educational robotics can offer and aid, once it can provide them a certain degree of independency in the exploration of environment. The system developed in this work allows the child to transmit the commands to a robot through myoelectric and movement sensors. The sensors are placed on the child's body so they can obtain information from the body inclination and muscle contraction, thus allowing commanding, through a wireless communication, the mobile entertainment robot to carry out tasks such as play with objects and draw. In this paper, the details of the robot design and control architecture are presented and discussed. With this system, disabled children get a better cognitive development and social interaction, balancing in a certain way, the negative effects of their disabilities. © 2012 IEEE.
Keywords: Control Architecture; Disabled Children; Mobile Entertainment Robot; Universal Design; Cognitive development; Control architecture; Design and control; Disabled children; Educational robotics; Mobile entertainments; Movement sensors; Muscle contractions; Myoelectric signals; Robot designs; Social interactions; Wireless communications; Machine design; Robotics; Robots; Sensors; Wireless telecommunication systems; Handicapped persons